A Study of Expansive Clay Treated With LRHA - Agus Setyo Muntohar, Roslan Hashim (2nd World Engineering Congress, 2002)
High swell and shrinkage is the characteristic of expansive clay soils. The soils swell in wet condition and tend to shrink in the dry. This form of behaviour will be a problem for roads and lightly loaded structures especially during seasonal fluctuation in groundwater table where the upper layer of the foundation soil will be affected. Chemical stabilizers, such as lime and Portland cement, are widely used to mitigate this problem. This paper presented the results of studies on the use of silica waste produced from rice husk combustion in Yogyakarta (Indonesia). The rice husk ash (RHA) and lime mixed, termed as lime-rice husk ash (LRHA) was used to stabilize expansive clay soil specimens. In the study, a series of laboratory tests was conducted. The results of the study show that LRHA reduced the heave of expansive clay and improved the geotechnical properties of specimens. The introduction of this soil stabilizer in road pavement construction will help to control volume compressibility due to moisture variation.